Implementation of Extracurricular Management : Implementasi Manajemen Ekstrakurikuler - Faizal Alif Hidayat; Nurdyansyah (Academia Open, 2021)
Management is essential for any activity or group in an effort to achieve the desired goal. Management activities consist of planning, organizing, placement, briefing, cultivation, communication, and decision making conducted by each organization with the aim to coordinate various resources owned by the company so that an efficient product or service is produced. Extracurricular activities are activities that are commonly done outside the classroom and outside the lesson hours to develop the potential of human resources owned by students, both related to the application of science obtained and in a special sense to guide learners in developing the potential and talents that exist in him develop the potential and talents that exist in him through mandatory activities and choices. Marching Band is a group of people who play one or more songs using a number of combinations of musical instruments (inflatable, percussion, and a number of instruments) together. The marching band's performance is a combination of the music (inflatable and punching) as well as the line-up action of the players.